1987
DOI: 10.1080/03015521.1987.10425582
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal frost tolerance of some ornamental, indigenous New Zealand plant species in the generaAstelia, Dicksonia, Leptospermum, Metrosideros, Phormium, Pittosporum, andSophora

Abstract: The frost hardiness temperature (i.e., the temperature that causes damage) and the lethal temperature (i.e., the temperature that causes death) were assessed in autumn (April-May), winter (July), spring (October), and summer (January) for 10 native plant species. The species in order of increasing winter hardiness/lethal temperature were Metrosideros kermadecensis and M. carminea ( -3/ -5°C), Sophora tetraptera and S. microphylla (-4/ -6°C), Leptospermum scoparium (-5/ -8°C), Sophora prostrata ( -6/ -11°C), Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 8 publications
(6 reference statements)
3
18
0
Order By: Relevance
“…In cases where minimum temperatures for field survival were given, these were translated into USDA hardiness zones ratings by translating the limits for zones into °C (viz Zone 10, +4.4 to -1.1°C; Zone 9, -1.2 to -6.6°C; Zone 8, -6.7 to -12.2°C; Zone 7, -12.3 to -17.7°C, Zone 6, <-17.7°C). Similar equivalences have been used by Warrington & Stanley (1987) and Warrington & Southward (1995). For the purposes of analysis, the few species with USDA hardiness ratings lower than Zone 6 (<-23.3°C) were usually grouped with Zone 6.…”
Section: Records Of Frost Damage and Minimum Temperaturementioning
confidence: 99%
“…In cases where minimum temperatures for field survival were given, these were translated into USDA hardiness zones ratings by translating the limits for zones into °C (viz Zone 10, +4.4 to -1.1°C; Zone 9, -1.2 to -6.6°C; Zone 8, -6.7 to -12.2°C; Zone 7, -12.3 to -17.7°C, Zone 6, <-17.7°C). Similar equivalences have been used by Warrington & Stanley (1987) and Warrington & Southward (1995). For the purposes of analysis, the few species with USDA hardiness ratings lower than Zone 6 (<-23.3°C) were usually grouped with Zone 6.…”
Section: Records Of Frost Damage and Minimum Temperaturementioning
confidence: 99%
“…Overall, therefore, within the range of species and cultivars studied, the frost tolerance limits are broadly similar to those for other New Zealand native species which have failed, under the comparatively mild oceanic winters experienced, to evolve the much greater hardiness limits of those taxa indigenous to the winter-cold, continental climates of North America and Eurasia (Sakai et al 1981;Warrington & Stanley 1987;Stanley & Warrington 1988;Greeret al 1989Greeret al , 1991.…”
Section: Resultsmentioning
confidence: 91%
“…Each of the species, cultivars, and hybrids studied showed the seasonal patterns of frost hardening and dehardening typical of most temperate plants (Weiser 1970;Larcher & Bauer 1981;Greer & Warrington 1982;Warrington & Stanley 1987;Greer et al 1991); the ability to tolerate frost was lowest during summer, it increased over a hardening phase to a maximum frost hardiness in winter, and progressively decreased over a dehardening phase in spring (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…although frost tolerance was investigated in some Phormium cultivars by Warrington & Stanley (1987), these were ornamental varieties of probable hybrid origin. Sparrow (1965) suggested that South Island plants have more rigid leaves and stronger fibres as a result of cold winters.…”
Section: Geographic Rangementioning
confidence: 99%